2022
DOI: 10.18280/ijsse.120109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Main Threats from COVID-19 on the Labor Market in the Context of Ensuring Economic Security

Abstract: The main research background involves identifying the factor that today, in the context of a pandemic and hostilities, the issue of labor migration, the labor market is an important problem for ensuring economic security. The main purpose of the article is to determine the major threats from COVID-19 and their impact on the labor market in the context of ensuring economic security. The basis of the methodology includes several theoretical methods for determining the key factors of influence and the method of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…One way or another, the COVID-19 pandemic asks for the latest rules for the introduction of activities and the introduction of the latest modern technologies. For example, Andriyiv et al (2022) used a range of modeling technologies to assess the state of the labor market in the context of COVID-19 pandemic. In general, a large number of scientists (Kuznyetsova et al, 2021) have proposed more and more new methods and technologies to study the problems of the negative impact of COVID-19 pandemic on professional activity in various fields.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One way or another, the COVID-19 pandemic asks for the latest rules for the introduction of activities and the introduction of the latest modern technologies. For example, Andriyiv et al (2022) used a range of modeling technologies to assess the state of the labor market in the context of COVID-19 pandemic. In general, a large number of scientists (Kuznyetsova et al, 2021) have proposed more and more new methods and technologies to study the problems of the negative impact of COVID-19 pandemic on professional activity in various fields.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings indicated that there is a sudden decrease in all trip purposes in the most critical COVID-19 periods, but there is an increase in trips made for errands because people are worried about a shortage of food or other essentials. COVID-19 pandemic has a huge economic impact in numerous countries, it has been an immediate and unfavorable influence on the labor market in all directions [9]. Many studies were carried out globally to investigate travel patterns and mode preferences during the pandemic [10].…”
Section: Introductionmentioning
confidence: 99%
“…Western European countries began discussions on unconditional basic income a few years before the COVID-19 pandemic [11][12]. However, at that time, scientists had a lot of controversy about understanding both the reasons for the introduction of such payments and the need.…”
mentioning
confidence: 99%